Reframing the competitiveness strategy of Bugis traders based on spiritual entrepreneurship after the COVID-19 pandemic in Indonesia - Thamrin, Andi; Ridjal, Syamsul; Syukur, Muhammad; Akib, Haedar; Syamsiar, Syamsiar (Linguistics and Culture Review, 2021)
The reframing of the competitiveness strategy of Bugis traders after the COVID-19 pandemic situation is oriented towards practicing the spiritual values ??of entrepreneurship. Reframing the Bugis trader's competitiveness strategy in the post Pandemic situation is oriented to the practice of spiritual values ??of entrepreneurship, as well as confirming public understanding that "the Bugis are the Black Chinese of Indonesia." Bugis traders who are characterized by spiritual entrepreneurship are strict on principle, "Resopa temmangingi mallomo naletei pammase Dewata" based on information and communication technology. This study combines normative research methods with descriptive methods in researching reframing the competitiveness strategies of Bugis traders who live on the shores of TempeLake, Indonesia. The results showed strengthening the basic values ??and orientation of the religious values ??of Bugis traders was a manifestation of reframing its strategy. There are basic values ??and orientations of social, economic values ??of Bugis traders based on spiritual entrepreneurship, namely faith, piety, morality, empathy or caring, visionary, fathonah, Amanah, siddiq, tabligh, istiomah. This strengthening of social, cultural, local economic values ??based on spiritual entrepreneurship supports the reframing of the competitive strategy of Bugistraders in transacting through market space as necessity to learn from large-scale social-distancing situations and enter NENOLE conditions.